(untitled) (Boulder, Colo., 2001)
This work faces the important issues in this region in the beginning of the 21st century. Designed as a core text for courses on Africa, it provides an analysis of history, politics, economics, class, ethnicity, the role of women and religious beliefs. It also assists the reader with maps and a glossary to enhance the text.
Keywords: Africa,Africa,Africa,Africa; Politics and government,Social conditions,Chính quyền và chính trị,Điều kiện xã hội; 1960-,1960-,1960-,1960-